Reflection of the Kurdish Issue in the American New York Times During the Period between (1961-1968) - Qaraman Haidar Rahman; Ismail Abdullah Ismail (Zanco Journal of Humanity Sciences)
The New York Times is an American newspaper based in New York City. The newspaper has a great influence on its readers internationally. The first issue was published on September 18, 1851 as the New York Daily Times. Throughout its life, it has been one of the most trusted newspaper organizations, winning dozens of international awards and consistently being one of the best-selling newspapers in the world. One of the topics that the newspaper focused on and devoted a lot of space to during the years (1961-1968) was the Kurdish issue in Iraq. On this basis, we conducted this scientific research entitled (Reflection of the Kurdish Issue in the American New York Times newspaper in the period between 1961-1968). It consists of an introduction and three axes. Each topic includes several discussions. In the first section, entitled (The Beginning of Defining the Kurds), we briefly highlighted some of these articles that dealt with the definition of Kurdish nationalism after the founding and publication of the newspaper. In the second section, we focused on the events of the Kurdish revolution and nationalist demands. The third and final topic was entitled (The role of the newspaper in demonstrating the international political position towards the Kurdish issue). In this topic, we highlight the international position and the newspaper’s position towards the Kurdish issue. Finally, we came to the conclusion that The New York Times provided a valuable service to the Kurdish cause in Iraq. Within the framework of his professional work.